Analysis of Safety & Pricing Issue in Grabs Car & The Solutions - Umairah Binti Buruhanutheen; Daisy Mui Hung Kee; Nurul Afiqah Binti Malik; Sunita A/P Kuson; Teh Yen; Siddhi Karlekar (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2019)
The following is a proposal for ride-hailing transport service, Grab. The proposal is done to assist them with the problems they face every now and then. Grabs Facebook page reveals myriad complaints about its services. Many app designers and even users have been facing several issues regarding their grab app. Since a lot of people rely on grab as their main transportation to go to places it is important for Grab to consider the criticism to improve their service. The main objectives definitely would be managing a good relationship with existing customers with a focus on creating loyalty towards their business. There are several solutions and recommendations that are included in this proposal to encourage Grab for their service enhancement. Keywords: Assist, Grab app, Price Issues, Safety, Good Relationship, Customers, Solutions